Childhood pemphigus foliaceus. Herpetiform variant. - Bonifazi, E.; Garofalo, L.; Pappalardi, M. (European Journal of Pediatric Dermatology, 2003)
The herpetiform variant of pemphigus foliaceus is characterized, besides the lack of mucosal lesions, by intense itching, circinate, papulo-pomphoid lesions, vesicles and crusts, good response to oral corticosteroids and benign clinical course. In children pemphigus foliaceus is rare and the herpetiform variant exceptional (1, 5). The histological examination (1, 3) shows superficial eosinophilic spongiosis. The immunofluorescence shows deposits of IgG e C3 in the intercellular space of epidermis. The diferential diagnosis should rule out dermatitis herpetiformis and IgA linear dermatitis (2, 4). The direct and indirect immunofluorescence, showing the typical intercellular deposits, is essential to rule out other disorders and confirm the diagnosis of pemphigus herpetiformis.